Somatic cell counts and total bacterial counts in goat milk - Kuchtík, Jan; Šustová, Květoslava; Kalhotka, Libor; Filipčík, Radek; Konečná, Leona; Kopec, Tomáš (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2023)
The main aim of our study was to evaluate the somatic cell count (SCC) and the total bacterial count (TBC) in the raw goat’s milk immediately after milking. The study was carried out in seven goats of the Brown Short-haired (BSH) breed during the whole lactation. An integral part of our study was to evaluate the effect of the stage of lactation (SL) on the daily milk yield (DMY), basic milk components (contents of fat, total protein and lactose), and pH of milk and relationships between all monitored indicators. All monitored goats were in the second lactation and throughout the study, all these goats were clinically healthy. Individual milk recording and sampling of each goat were carried out on the mean 64, 109, 146, 181 and 218 day of lactation. During milk recording and sampling all monitored goats were milked by hand. During lactation, the mean values of Log SCC ranged from 3.68 to 7.16 and the mean values of Log TBC from 5.30 to 9.49, whilst the SL had a significant (p ≤ 0.01) influence on both of these indicators. Both the Log SCC and the Log TBC had a significant (p ≤ 0.01) correlation only with the content of lactose, whilst both of these correlation were negative. However, the correlation between the Log SCC and the Log TBC was significanly (p ≤ 0.05) positive. Regarding the effect of the SL on all other monitored traits, this factor had a significant (p ≤ 0.01) effect on the DMY and contents of all basic milk components. Nevertheless, the SL had no significant effect on pH. Despite the fact that the SL had a significant (p ≤ 0.01) effect on the fat and protein contents, in general it can be stated that their contents were quite variable. On the other hand the contents of lactose gradually decreased during lactation. In conclusion, it can be stated that the results of our study suggest that the content of lactose may be a good predictor of both the SCC and the TBC and that when the SCCs increase the TBCs also increase and vice versa.